The Ideological-Conflict Hypothesis: Intolerance Among Both Liberals and Conservatives. (February 2014) - Brandt, Mark J.; Reyna, Christine; Chambers, John R.; Crawford, Jarret T.; Wetherell, Geoffrey
Decades of research in social and political psychology have demonstrated that political conservatives appear more intolerant toward a variety of groups than do political liberals. Recent work from our three independent labs has challenged this conventional wisdom by suggesting that some of the psychological underpinnings of intolerance are not exclusive to people on either end of the political spectrum. These studies have demonstrated that liberals and conservatives express similar levels of intolerance toward ideologically dissimilar and threatening groups. We suggest directions for future research and discuss the psychological and political implications of our conclusions.